(untitled) (Música Hodie, 2024)
Reciting the Tang Dynasty jinti shi (recent-style poetry) or yinsong reveals the classical orality and literacy of ancient Chinese text that has had a long history since 619 CE. However, the lack of musical analysis of the jinti poetry yinsong based on its performance practice in past studies resulted in an absence of specificities on the principles that govern its authentic oral expression, including structure, prosody, voice inflection, and rhythm pattern. In this article, we aim to revisit the neglected aspects such as syntactic structure, language tone and stress, prosodic rhythm, and the musical relationship between different metrical patterns and syllable types in the recitation of jinti poetry from the Henan region. We triangulate data from past literatures, recordings, and two surviving cultural bearers. We hope to offer a reference on the principles of yinsong, providing a closer step to an authentic jinti poetry yinsong. This may enhance contemporary interpretation and understanding of this intangible cultural heritage.